Discernment as Critique in Teresa of Avila and Erasmus of Rotterdam. (June 2014) - F, C M.
Abstract : This essay interprets recent interest in "surface reading" or "just reading" as one manifestation of widespread interest in finding alternatives to critique. Noting that critique and its alternatives alike have been notably secular in their self-understanding as in their sources, this essay turns instead to premodern religious sources and argues that their explicit concern with questions of judgment and interpretation provides unexpected resources for reviving critique. In brief, I argue that the process of discernment on display in mystic texts by Teresa of Avila and humanist writings by Erasmus of Rotterdam offer a more holistic vision of critique's project.